2010
DOI: 10.1007/s10554-010-9634-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective diagnostic cardiovascular imaging: when does it provide good value for the money?

Abstract: To summarize the results of all original cost-utility analyses (CUAs) in diagnostic cardiovascular imaging (CVI) and characterize those technologies by estimates of their cost-effectiveness. We systematically searched the literature for original CVI CUAs published between 2000 and 2008. Studies were classified according to several variables including anatomy of interest (e.g. cerebrovascular, aorta, peripheral) and imaging modality under study (e.g. angiography, ultrasound). The results of each study, expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…However, the scale has been analyzed and reported on in several previous publications, which found that the quality score was correlated with factors such as the methodology used to conduct and report results of sensitivity analyses, as well as the quality and experience of journals reporting results from economic evaluations [18,21,22,26,46]. We did not judge the appropriateness of the comparator used in the incremental cost-effectiveness ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the scale has been analyzed and reported on in several previous publications, which found that the quality score was correlated with factors such as the methodology used to conduct and report results of sensitivity analyses, as well as the quality and experience of journals reporting results from economic evaluations [18,21,22,26,46]. We did not judge the appropriateness of the comparator used in the incremental cost-effectiveness ratios.…”
Section: Discussionmentioning
confidence: 99%
“…CUA has been applied to a wide variety of health interventions including pharmaceuticals [18], surgical procedures [19,20], and diagnostic imaging [21,22] and is recommended by many experts in health economics and outcomes research. One previous study reviewed various types of published cost-effectiveness analyses involving all kinds of diagnostic strategies [23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it enables the sooner and better therapy with relatively low financial resources (Picano, 2005;Otero et al, 2010). Moreover, it is of great scientific and educational value (Maecken et al, 2011;Evangelista et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This often results in long term, potentially life-long surveillance, with not only direct costs of imaging but also potential opportunity costs of foregoing another preventive measure in health systems with scarce resources. However, similar to other imaging interventions, US has been shown to be overall highly cost-effective than no imaging or observation alone [15]. There are conflicting results on quality of life, anxiety and depression associated with long-term screening [1], with some studies showing mild transient reduction of quality of life [14].…”
Section: Conflict Of Interest Nonementioning
confidence: 99%